2020
DOI: 10.1108/maj-03-2019-2224
|View full text |Cite
|
Sign up to set email alerts
|

CEO characteristics and bank performance: evidence from India

Abstract: Purpose The purpose of this study is to examine the impact of chief executive officer (CEO) personal characteristics on the performance of Indian commercial banks. Additionally, it also analyses the nonlinear relationship of CEO age and CEO tenure on the bank performance. Design/methodology/approach A balanced panel data approach has been used in this study. Particularly, the fixed effect estimation technique is used to examine the relationship between CEO characteristics and bank performance during the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 132 publications
(156 reference statements)
7
50
1
Order By: Relevance
“…These findings are consistent with earlier investigations managing the estimation of the correlation between female representation in boardrooms and performance in advanced economies [3,13,63] and in rising economies [64,65]. Table 3 shows that duality positively affects commercial banks' financial performance CBs [31,66]. This result confirms and supports the second hypothesis (H2) of the study, which means that a duality can run and administer the bank obviously and consistently to expand the bank's consequences.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with earlier investigations managing the estimation of the correlation between female representation in boardrooms and performance in advanced economies [3,13,63] and in rising economies [64,65]. Table 3 shows that duality positively affects commercial banks' financial performance CBs [31,66]. This result confirms and supports the second hypothesis (H2) of the study, which means that a duality can run and administer the bank obviously and consistently to expand the bank's consequences.…”
Section: Resultssupporting
confidence: 91%
“…We found that CEO duality [31,75] had a positive and significant impact on bank financial performance. The focus of decision-making with the sole individual is excellent for the strength of the Chinese CBs by increasing business decisions and diminishing the delay in its accomplishment.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The author applied tobit regression to analyze the panel data from 38 commercial banks (24 government-owned banks and 14 private commercial banks) listed in the Bombay Stock Exchange, and documented a better performance by private commercial banks than the government-owned commercial banks. Using balanced panel data from 36 commercial banks (21 government-owned and 15 private commercial banks), Gupta and Mahakud (2020) assessed CEO characteristics and firm performance. Behara et al (2015) examined IT adoption and firm performance using the data from nationalized commercial banks and IT firms.…”
Section: Past Studiesmentioning
confidence: 99%
“…As the education level increases, a CEO becomes more engaged and had practical experience in their field. Gupta and Mahakud ( 2020 ) show that the education of CEO increases bank performance. Elsharkawy et al ( 2018 ) found a positively insignificant relationship between CEO's education and bank performance.…”
Section: Introductionmentioning
confidence: 99%